Nanotechnology in dentistry: Current achievements and prospects - Ramandeep Singh Gambhir; G M Sogi; Ashutosh Nirola; Rajdeep Brar; Tegbir Sekhon; Heena Kakar (Journal of Orofacial Sciences, 2013)
Nanotechnology offers advances particularly in each and every field of human activity such as electronics, industry, telecommunications, environmental science, etc., The field of nanotechnology has got remarkable potential that can bring considerable improvements to the human health, enhanced use of natural resources, and reduced environmental pollution. Since 1990s, nanotechnology has been exploited for potential medical and dental applications. Nanotechnology holds promise for advanced diagnostics, targeted drug delivery, and biosensors. Dentistry is undergoing yet another change to benefit mankind, this time by transforming itself to the nanodentistry. A variety of nanostructures such as nanorobots, nanospheres, nanofibers, nanorods, etc., have been studied for various applications in dentistry and medicine. Preventive dentistry has also utilized nanodentistry to develop the nanomaterials for inclusion in a variety of oral health-care products. However, due to insufficient evidence on potential hazards on human health and environment, nanotechnology has become a controversial issue. It is documented that nanomaterials can enter the human body through several routes and can pose a threat to human health by interacting with the DNA. The present article focuses on the current status and the future implications of nanotechnology in dentistry.